Investigation of near wall wake induced aeroacoustic noise by simultaneous use of particle image velocimetry, microphones and wall pressure sensors. (1st January 2011) - Ruiz, T.; Borée, J.; Sicot, C.; Brizzi, L-E.; Gervais, Y.
The aeroacoustic study of the wake of a disk (diameter D ) located at a distance H of a wall is experimentally realised at the Reynolds number ReD = 130, 000. By combining measurements in the near and far field, the objective is to identify the acoustic source mechanisms and analyse the relation between the turbulent flow and the acoustic emission. Simultaneous measurements between wall pressure sensors and one microphone in the far field allow us to calculate the spatio-temporal correlations. The slope of the correlation peaks can be related to an acoustic source located in the mean recirculating bubble. The PIV measurements simultaneously recorded with the acoustic pressure confirm that an acoustic flow source is located in the mean recirculating bubble. A method using stochastic estimation to resample the PIV measurements (1 Hz) at the pressure acquisition frequency (5.12 kHz) is also proposed.